What Made a Place Holy in Early Islam? An Inquiry into Meaning and Doctrinal Modalities - Ayyad, Essam (Journal of Al-Tamaddun, 2024)
Compared to other religious systems rooted in Late Antiquity, Islam placed greater emphasis on the transcendent, assigning less value to physical forms per se. This article seeks to explore conceptions relating to what made a place ‘holy’ in early Islamic places of worship, delving into understanding the significance of sacred spaces in Islam, and dissecting the procedures and beliefs instrumental in the consecration of such locations. The primary focus rests on mosques, which were deemed the pinnacle of sacred spaces during the nascent Islamic period. This discourse deliberately omits discussion on Islamic funerary structures, which emerged in the classical form later in the third/ninth century. Instead, it analyzes the cases of the Ka’ba in Mecca and the Prophet’s mosque in Medina. The former serves as an exemplar of Islamized sanctuaries, whereas the latter epitomizes the prevalent archetype of sacred spaces in early Islam.